2009
DOI: 10.4261/1305-3825.dir.2584-09.1
|View full text |Cite
|
Sign up to set email alerts
|

Defecography: a practical approach

Abstract: The purpose of this pictorial essay is to describe the main morpho-functional imaging features, physiological and pathological, of the recto-anal region and pelvic floor as depicted with conventional video defecography.Defecography has dramatically improved our knowledge of dysfunctions of evacuation. The most frequent indications and related disorders are presented from a database of more than 2500 examinations conducted in two radiology departments over a period of 15 years.Imaging features of the common rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Despite their low prevalence, their detection is important in the planning of the correct therapeutic approach. Conventional radiology is currently considered as the gold standard [5,7,8], because is a cost-effective procedure, simple to perform, and widely available [19]; however, it is an invasive procedure, especially if it is performed with four contrast that uses ionizing radiation and visualizes only the lumen of the opacified organs. MRI Defecography was first described by Yang et al in 1991 [7,31], is a less-invasive imaging modality that allows a multiplanar and multiparametric evaluation of the three pelvic compartments, also visualizing soft tissue, in a single procedure without exposure to ionizing radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Despite their low prevalence, their detection is important in the planning of the correct therapeutic approach. Conventional radiology is currently considered as the gold standard [5,7,8], because is a cost-effective procedure, simple to perform, and widely available [19]; however, it is an invasive procedure, especially if it is performed with four contrast that uses ionizing radiation and visualizes only the lumen of the opacified organs. MRI Defecography was first described by Yang et al in 1991 [7,31], is a less-invasive imaging modality that allows a multiplanar and multiparametric evaluation of the three pelvic compartments, also visualizing soft tissue, in a single procedure without exposure to ionizing radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Under normal conditions, it is expected that the mean anorectal angle, at rest, is 95º, with a physiological variation of 65-100º (4) . With contraction, the angle should decrease and become more acute, whereas it should increase, becoming more obtuse, due to straightening of the rectum, during evacuation.…”
Section: Methodsmentioning
confidence: 99%
“…Defecography is a diagnostic tool that demonstrates both physiologic and pathologic properties of the pelvic floor functionally and morphologically. Investigators who reviewed more than 2,500 reports in the previous 15 years in two different radiology departments concluded that defecography is the gold standard for the diagnosis of rectocele, enterocele, and pelvic floor disorders such as intussusception [13].…”
Section: Discussionmentioning
confidence: 99%